2012
DOI: 10.5833/jjgs.45.961
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary Malignant Solitary Fibrous Tumor of the Pancreas

Abstract: 再発を来した膵原発 malignant solitary fibrous tumor の 1 例 山梨 高広 1) 鳥海 史樹 1) 矢作 雅史 1) 白鳥 史明 1) 五十嵐一晴 1) 西 知彦 1) 半田 寛 1) 関根 和彦 1)により膵尾部腫瘤を指摘され,精査加療目的にて当院受診となっ た.腹部 CT 上,膵尾部に 9 cm および 3 cm 大,膵頭後部に 3 cm 大の腫瘤を認めた.膵頭後部リンパ節転 移をともなう膵尾部悪性内分泌腫瘍を疑い,膵体尾部切除を施行したが,切除標本の免疫組織化学染色検 査にて孤立性線維性腫瘍(solitary fibrous tumor;以下,SFT と略記)と診断された.また凝固壊死巣およ び多数の核分裂像が認められ,malignant SFT が疑われた.術後 21 か月後の腹部 CT にて膵局所再発を認め たが,手術は希望されず,化学放射線療法を施行後,経過観察中である.SFT は比較的まれな腫瘍であり, 多くは胸膜に関連した胸腔内病変として発生する.膵臓原発の SFT 報告例は極めてまれであり,再発を含 め悪性の転帰をたどった症例は自験例のみである.貴重な症例と考え,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Staining is also negative for S-100, which is positive for neurogenic tumors, and negative for c-kit, which is positive for GIST. These features are useful for distinguishing SFT from other mesenchymal tumors [ 6 , 19 ]. Recently, it was revealed that NAB2–STAT6 fusion was the driver mutation in SFT, and the transcriptional repressor of the cell division pathway is converted to the transcriptional activator [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staining is also negative for S-100, which is positive for neurogenic tumors, and negative for c-kit, which is positive for GIST. These features are useful for distinguishing SFT from other mesenchymal tumors [ 6 , 19 ]. Recently, it was revealed that NAB2–STAT6 fusion was the driver mutation in SFT, and the transcriptional repressor of the cell division pathway is converted to the transcriptional activator [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, experience with SFT is very limited. Our current understanding of this tumor is mainly based on individual case reports 12–44 . In this study, we analyzed 9 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The patient with intermediate-risk SFT is alive with no evidence of disease at 62 months’ follow-up. However, among previously published primary pancreatic SFTs, there are 7 cases that were reported as a malignant SFT 25,31,34,36,41–43 . These tumors were characterized with marked cellularity (reported in 5 of 7 cases), nuclear pleomorphism and/or atypia (reported in 4 of 7 cases), necrosis (reported in 5 of 7 cases) and frequent (up to 25/10 HPF) mitoses (reported in all 7 cases).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations